Tadris Maharah al-Kitabah bi al-Kalimah al-Mutaqathi'ah - Hamdy, Mohammad Zainal; Muhammad, Jiddah Hassan (Al-Wazan: Journal of Arabic Education, 2024)
Teachers play an important role in the reading skills learning process. Apart from being teachers, teachers are also teachers who are always required to provide interesting, effective and efficient learning. The aim of this research is to explore more deeply about learning writing skills using crossword puzzles, apart from anything that can help the activity process. In this research, researchers used a qualitative approach with a library method where the data source came from credible books according to the topic of discussion. The results of the research are the steps for learning reading skills starting with 3 important aspects, namely Introduction, Process, and Conclusion or Correction from the teacher. Previously acquired language skills as well as learning experience and a strong mental aspect can help make it easier to achieve the goals in this learning.